Pengaruh Konflik Interpersonal Dan Beban Kerja Terhadap Stres Kerja Pegawai Pada Kantor Perwakilan BKKBN Provinsi Sulawesi Selatan - Marson Marson; Rina Rina; Kamaruddin Kamaruddin (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The aim is to understand how interpersonal conflict and workload influence how work stress at the South Sulawesi Province BKKBN Representative Office was surveyed to obtain primary data. Saturated sampling was used in this study, and a total of 98 people were sampled. The validity and reliability of these findings have been evaluated, through tests of heteroscedasticity, multicollinearity, and normality have all been considered. The data analysis method uses multiple regression.